The struggle for autonomy on Nicaraguas Atlantic Coast / Ana K. Carrión - Carrión, Ana K. (1999)
This study of the process of autonomy on Nicaragua's Atlantic Coast analyzes the disjunctive nature of the autonomy movement as interpreted through two distinct visions: one of indigenous nationalism and the other of a regional and multi-ethnic character. The persistence of these two visions has been one of the strongest obstacles to achieving true autonomy for the Atlantic Coast region. A close examination shows that indigenous nationalism and ethnic appropriation of autonomy have been the underlying forces behind the construction of these two visions. Ethnic claims for autonomy are traced back to the identity and the politics of identity, which are now asserting themselves through nationalistic or semi-nationalistic expressions. This has significantly contributed to the inability of Costeño society to reach a consensus on a clear definition of autonomy. For the present autonomy scheme to be successful, Costeños will need to coalesce around a common, and more regional, identity that can adequately address the ethnic cleavages